Tunneling and Propping through Related Party Transactions in Pakistani Family Business Groups - Hussain, Shahid; Safdar, Nabeel; Abbas, Muhammad (The journal of contemporary issues in business and government, 2022)
The aim of this study is to analyze the agency issues like tunneling and propping while examining the impact of Related Party Transactions (RPTs) in firms with respect to family business groups of Pakistan.This study used a sample of 326 non-financial firms listed on Pakistan Stock Exchange in the period from 2008 to 2013 by examination of over four thousand five hundred RPTs. For data analysis, panel regression models with both firm and year fixed effects as well as logit model are applied.The findings depict that controlling shareholder in firms affiliated with family business groups mostly tunnel resources through cash payments and trade of goods & services and prop up resources through cash receipts transactions. The study also finds that tunneling related transactions are more significant in firms that have larger size, market value and other receivables balances. Whereas, propping related transactions are dominant in highly leveraged firms with lower return on assets.This study is limited to Pakistani nonfinancial sector. The results implied that interests of minority shareholders are considerably affected by the hidden operations of the majority shareholders in family business group firms. The minority shareholders need to be more cognizant of the family business group firms’ ownership structures, board members, directors’ shareholding and related party transactions.This study provides new insights on ‘propping’ besides ‘tunneling’ in Pakistani family-owned companies, which has received little attention in the context of emerging economies, and Pakistan.